CS-34 Increased prevalence of nocturnal hypertension and attenuated blood pressure dipping in pediatric SLE. (August 2018) - Wenderfer, Scott E; Fallon Campbell, J; Jose, Steffy; Archila, Mario; Matloff, Robyn; Mynarski, Kari; Jack Weaver, D; Hoffman, Sarah; Nelson, Jessica; Kallash, Mahmoud; Brunner, Hermine; Mitsnefes, Mark
Abstract : Background: The optimal goals for blood pressure management in SLE are unknown. Uncontrolled blood pressure is a known risk factor for cardiovascular disease. The increased cardiovascular risks associated with SLE are not fully explained by traditional risk factors, such as hypertension and dyslipidemia, at least when based on definitions established for individuals without SLE. One possibility is that the patterns of blood pressure dysregulation in SLE may differ from those in otherwise healthy individuals or patients with obesity/metabolic syndrome. Methods: The BPpSLE study is a cross-sectional multicenter analysis of blood pressure patterns in children with SLE. Inclusion criteria:≥4 ACR classification criteria for SLE and age <21 years. Exclusion criteria: intravenous steroid use within past month, glomerular filtration rate <60 mL/1.73 m 2 /min, or kidney transplant. Interim analysis was performed on the initial 52 subjects enrolled. Participants were assessed once over 24 hours by ambulatory blood pressure monitoring, using routine equipment and SpaceLabs software. Diurnal and nocturnal averages for both systolic and diastolic blood pressure were assessed, and nocturnal blood pressure dipping was calculated as difference between median awake and sleep measurements. In addition, blood pressure loads were calculated as percentages of measurements that exceeded validated, age-specific thresholds for normal blood pressure. Nocturnal hypertension was defined as systolic or diastolic load during sleep of >25%. Enrollment in the BPpSLE study is open to all interested CARRA investigators. Results: The cohort is 79% female, 29% Hispanic and 27% black. Median age was 16.3 years (IQR 13–17) at time of testing. Median SLEDAI was 4 (IQR 2–11), renal SLEDAI was 0 (IQR 0–4), and median glomerular filtration rate was 104 mL/1.73 m 2 /min (IQR 91–114). Nocturnal hypertension was seen in 47% and attenuated dipping was seen in 71% of children with SLE, compared to 39% and 26% of historical controls. Loads were 14% and 13% while sleeping verses 5% systolic and 6% diastolic while awake. This corresponded with median nocturnal dipping of 6% in systolic and 13% in diastolic blood pressures (normal >10%). Conclusions: There is a high prevalence of both nocturnal hypertension and attenuated nocturnal blood pressure dipping in out SLE cohort, compared to an age-matched adolescent population with borderline high blood pressure. These patterns are not due to renal failure or active nephritis. Although most SLE patients in the cohort do not meet criteria for diagnosis of hypertension, the degree of dysregulation could potentially contribute to the cardiovascular risk noted in SLE. Acknowledgements: This abstract is being presented on behalf of the Midwest Pediatric Nephrology Consortium (MWPNC).